2024
DOI: 10.3389/fpls.2023.1292272
|View full text |Cite
|
Sign up to set email alerts
|

Termiticidal, biochemical, and morpho-histological effects of botanical based nanoemulsion against a subterranean termite, Odontotermes Formosanus Shiraki

Raghda Nasser,
Ezzeldin Ibrahim,
Hatem Fouad
et al.

Abstract: Recently, the use of nanopesticides has shown significant efficacy in the control of many pests. However, the effect of nanopesticides, especially nanoemulsions, on suppressing termites, Odontotermes formosanus (Shiraki, 1909) (O. formosanus), has not been studied yet. Therefore, this study aimed to produce nanoemulsions of the essential oils of eucalyptus (Eucalyptus globulus Labill; E-EO) and nutmeg (Myristica fragrans Houtt; N-EO) to suppress O. formosanus. The analysis of eucalyptus nanoemulsion (E-NE) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
2
2
0
Order By: Relevance
“…Through the utilization of triboelectric forces and the surface effect, nanostructured alumina absorbs onto the wax layer, causing the cuticle to become dehydrated [ 63 ]. This study’s findings are supported by Nasser et al [ 37 ], who observed modifications in O. formosanus workers following treatment with Myristica fragrans and Eucalyptus globulus nanoemulsions.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Through the utilization of triboelectric forces and the surface effect, nanostructured alumina absorbs onto the wax layer, causing the cuticle to become dehydrated [ 63 ]. This study’s findings are supported by Nasser et al [ 37 ], who observed modifications in O. formosanus workers following treatment with Myristica fragrans and Eucalyptus globulus nanoemulsions.…”
Section: Resultssupporting
confidence: 88%
“…Furthermore, the integrity of the midgut can be studied as an indication of sensitivity to a variety of harmful substances [ 64 ]. The outcomes of this investigation are corroborated by Nasser et al [ 37 ], who saw changes in the typical structure of O. formosanus workers after treatment with M. fragrans and E. globulus nanoemulsions. Following treatment with biosynthesized silver nanoparticles, Abou El-Enain et al [ 65 ] showed histopathological indicators in the midgut tissues of Agrotis ipsilon .…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…AgNPs can be synthesized using various methods, including physical, chemical, and biological approaches [ 27 , 32 , 33 , 34 ]. However, biological methods are considered safer and more environmentally friendly compared to conventional physical and chemical methods [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%